2022
DOI: 10.24912/tmj.v4i2.17524
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan penggunaan kosmetik bedak padat terhadap kejadian akne vulgaris pada mahasiswi Fakultas Kedokteran Universitas Tarumanagara

Abstract: Akne Vulgaris merupakan penyakit kulit yang sering terjadi di kalangan dewasa muda. Kejadian tertinggi akne vulgaris dijumpai pada usia 17-21 tahun. Faktor penyebabnya dapat dikarenakan penggunaan kosmetik seperti bedak padat. Kosmetik jenis bedak padat yang bersifat bahan komedogenik dan aknegenik akan memicu terjadinya komedo dan menyebabkan akne vulgaris. Tujuan dari penelitian ini adalah untuk mengetahui penggunaan kosmetik bedak padat dan hubungannya terhadap kejadian akne vulgaris pada mahasiswi Fakultas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The most age of FK UNISSULA students who use waterproof foundation containing dimethicone and most affected by AV are 20 years old with a percentage of 14.9%. This is in accordance with research conducted by Andriana et al (2014) concerning the relationship between the use of facial cosmetics and the onset of AV, it was found that the prevalence of respondents was 59.1% experiencing AV with the age range of the respondents being 16-20 years and 84.8%. respondents use cosmetics and the rate of AV incidents is more common in respondents who use cosmetics.…”
Section: Discussionsupporting
confidence: 91%
“…The most age of FK UNISSULA students who use waterproof foundation containing dimethicone and most affected by AV are 20 years old with a percentage of 14.9%. This is in accordance with research conducted by Andriana et al (2014) concerning the relationship between the use of facial cosmetics and the onset of AV, it was found that the prevalence of respondents was 59.1% experiencing AV with the age range of the respondents being 16-20 years and 84.8%. respondents use cosmetics and the rate of AV incidents is more common in respondents who use cosmetics.…”
Section: Discussionsupporting
confidence: 91%
“…Experiencing negative body image can have significant effects on an individual's attitudes and self-confidence when interacting in social life. As research by Harlim et al (2019) indicates, skin issues such as acne, despite not having serious medical impacts, can lead to significant psychosocial effects. Participants often experience a lack of confidence when communicating with people around them, especially because they feel uncomfortable with their skin issues.…”
Section: Discussionmentioning
confidence: 99%